2012
DOI: 10.1017/s003329171200147x
|View full text |Cite
|
Sign up to set email alerts
|

Global prevalence of anxiety disorders: a systematic review and meta-regression

Abstract: Anxiety disorders are common and the substantive and methodological factors identified here explain much of the variability in prevalence estimates. Specific attention should be paid to cultural differences in responses to survey instruments for anxiety disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

40
787
13
45

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 1,216 publications
(885 citation statements)
references
References 54 publications
40
787
13
45
Order By: Relevance
“…2006; Baxter et al. 2013), and secular trends were not observed in relation to the prevalence of total anxiety 4 (Baxter et al. 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2006; Baxter et al. 2013), and secular trends were not observed in relation to the prevalence of total anxiety 4 (Baxter et al. 2014).…”
Section: Discussionmentioning
confidence: 99%
“…studies 39 Meta‐analysis: yes Adults Range: 500–20,000 Community surveys using probability samplingDiagnostic criteria, standardized instruments or clinician diagnosis Pooled one‐year and lifetime prevalence of: Total anxiety disorders: 10.6% (7.5, 14.3), 16.6% (12.7, 21.1) PD: 1.0% (0.6, 1.5), 1.2% (0.7, 1.9) Agoraphobia: 1.6% (1.0, 2.3), 3.1% (2.1, 4.4) SAD: 4.5% (3.0, 6.4), 2.5% (1.4, 4.0) SP: 3.0% (1.0, 5.8) and 4.9% (3.4, 6.8) OCD: 0.5% (0.3, 0.9), 1.3% (0.9, 1.8) GAD: 2.6% (1.4, 4.2), 6.2% (4.0, 9.2) Anxiety higher in women SAD rates decline with age Switzerland, US: 23–28.7; Korea: 9.2 Baxter 2013 Search: 2009 # incl. studies 87 Meta‐analysis: yes 44 countries across the globe Median: 2419 Community samplesInterview schedules, semi‐structured instruments, diagnostic instruments that mapped to DSM or ICD Global prevalence: 7.3% (4.8–10.9) 5.3% (3.5, 8.1) in African & 10.4% (7.0, 15.5) in Euro/Anglo cultures Women 2× men; younger people more affected Adults 55 + 20% less anxiety than 35–55 20–50% lower risk in cultures compared to Euro/Anglo Mirza 2004 Search: March 2002 # incl.…”
Section: Embasementioning
confidence: 99%
See 1 more Smart Citation
“…The abundance of published scientific literature indicates the efforts devoted to understand the biology of neurocognitive processing of stressful stimuli and the pathophysiology associated with these processes. Although these efforts have produced therapeutically useful pharmacologic treatment strategies, the abuse potential and side effects of these agents, their limited usefulness in pediatric and elderly population, and women [2] combined with increasing global burden of anxiety-related disorders [3,4] is driving the search for better treatment strategies fort these disorders. Varying definitions and techniques of inducing stress, difficulties in connecting animal and human behavior to specific neuronal pathway and the nature of evolving diagnostic criteria present additional challenges.…”
Section: Introductionmentioning
confidence: 99%
“…Disorders with pathologies that include anxiety-related debilitating psychological and physiologic responses are widespread in the U.S. and according to one report about 18% of adults may seek treatment for anxiety disorder [7]. A recent study analyzed global burden and regional occurrence of anxiety disorders and estimated that the prevalence of anxiety disorders was 7.3% and ranged from 5.3% in African cultures to 10.4% in Euro/Anglo cultures [3,4]. Continuous presence of images of natural and man-made disasters including presence of terrorist atrocities on widely circulated digital media has added to the sources of potentially anxiogenic stimuli and it has been suggested that global burden of anxiety disorders will increase significantly [1,8].…”
Section: Introductionmentioning
confidence: 99%